Complete chloroplast genome sequence of Adenophora remotiflora (Campanulaceae). (3rd July 2016) - Kim, Kyung-Ah; Cheon, Kyeong-Sik; Jang, Su-Kil; Yoo, Ki-Oug
Abstract: The complete chloroplast genome of Adenophora remotiflora was determined in this study. The total genome size was 171 724 bp in length, containing a pair of inverted repeats of 27 437 bp, which were separated by large single copy and small single copy of 105 555 bp and 11 295 bp, respectively. The overall GC contents of the plastid genome were 38.8%. One hundred and twelve unique genes were annotated, including 78 protein coding genes, 30 tRNA genes and 4 rRNA genes. In these genes, 15 genes contained one intron and 2 genes had two introns. A phylogenetic tree showed that Adenophora remotiflora was closely related to Hanabusaya asiatica .